Sebaran Cemaran Hg di Kawasan Pertambangan Emas Rakyat Menggunakan Metode Inverse Distance Weight - Kusdarini, Esthi; Malik, Abd.; Utamakno, Lakon; Budianto, Agus (Universitas Riau, 2021)
Gold mining on mining communities supports economic life for the societies. On the other hands, these activities are not only support the economic but also give bad effects to the environment. Some people are still using amalgamation process to gold ore process which has the potential to spread Hg concentration in the main area. Spatial distribution of Hg concentration was found in this study. The purpose of this research was identifying the contamination of Hg concetration in three villages of society’s mining gold areas in Kertajaya Sukabumi, West Java. Those three villages were Cigadog Village, Pondok Tilu Citamiang Village, and Kiara 2 Village. Hg concentration distribution map was obtained several samples which were taking 6 soil samples in Cigadog village, 5 soil samples from Pondok Tilu Citamiang Village, and 4 soil samples in Kiara 2 Village. Those samples were analysed for Hg concentration using AAS (Atomic Absorption Spectrophotometer) method. Inverse Distance Weight method was used as Data processing and it was helped by ArcGIS software. The result showed that soil samples from Cigadong village contained Hg concentration of 0.28 - 2.84 ppm, 83% samples were critically polluted, and the contaminated areas were 5.888 hectares. Whilst, soil samples from Pondok Tilu Citamiang Village contained Hg concentration of 0.14 - 1.26 ppm, 80% samples were critically polluted, and the polluted areas were 1.476 Ha. Then, soil samples from Kiara 2 Village contained Hg concentration of 0.67-6.19 ppm, 100% samples were critically polluted, and the contaminated area was 0.040 hectare. The findings of the contaminated area and the pollutant level in mining societies in Kertajaya Village, Sukabumi could be used as initial input for the efforts to restore the Hg polluted environment.